2022
DOI: 10.46367/jps.v3i1.479
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Social Reporting Factors For The Indonesian Islamic Commercial Banks

Abstract: Islamic social reporting as part of the responsibility of Islamic banks in fulfilling Islamic social performance reporting can also be a priority for investors in making investment decisions. The use of the Islamic social reporting Index in the disclosure of company reports aims to fulfill investors' spiritual desires in the form of accountability to Allah. This study aims to determine the effect of firm age, firm size, and profitability on Islamic social reporting disclosure in Indonesian commercial banks. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
3

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 10 publications
1
3
0
3
Order By: Relevance
“…(Wardani & Sari, 2018). Other studies also argue that company size has an insignificant effect on ISR at Indonesian Commercial Banks (Sukardi et al, 2022). Formulated hypothesis is:…”
Section: Company Sizementioning
confidence: 97%
See 1 more Smart Citation
“…(Wardani & Sari, 2018). Other studies also argue that company size has an insignificant effect on ISR at Indonesian Commercial Banks (Sukardi et al, 2022). Formulated hypothesis is:…”
Section: Company Sizementioning
confidence: 97%
“…In addition, other studies have shown that profitability does not have a significant effect on CSR (Syahierah & Larasati, 2019). The company's profitability has an insignificant effect on the ISR of Indonesian Commercial Banks (Sukardi et al, 2022). Based on theoretical studies and empirical studies that have been described, hypotheses can be formulated:…”
Section: Profitabilitymentioning
confidence: 99%
“…Faktor ukuran perusahaan dalam mempengaruhi pengungkapan ISR sudah dilakukan penelitian oleh Umiyati dan Baiquni (2018); Prasetyoningrum (2018); Pratama, Muchlis, and Wahyuni (2018); Puspasari and Muzakki (2021); Sukardi, Widiatmini, and Fachrurazi (2022) dengan hasil yang beragam, tetapi penelitian tersebut tidak membahas mengenai ukuran DPS. Faktor ukuran DPS dalam mempengaruhi pengungkapan ISR sudah dilakukan penelitian oleh Murdiansyah (2021); Prihatiningsih and Hayati (2021) dengan hasil yang berbeda, akan tetapi penelitian tersebut tidak membahas tentang FDR, ukuran perusahaan dan umur perusahan.…”
Section: Faktor-faktor Yang Mempengaruhi Pengungkapan Islamic Social ...unclassified
“…Faktor ukuran DPS dalam mempengaruhi pengungkapan ISR sudah dilakukan penelitian oleh Murdiansyah (2021); Prihatiningsih and Hayati (2021) dengan hasil yang berbeda, akan tetapi penelitian tersebut tidak membahas tentang FDR, ukuran perusahaan dan umur perusahan. Selanjutnya faktor umur perusahaan dalam mempengaruhi pengungkapan ISR sudah dilakukan penelitian oleh Widiyanti and Hasanah (2017); Prasetyoningrum (2018); Puspasari and Muzakki (2021); Irbah, Praptiningsih, and Setiawan (2021); Sukardi, Widiatmini, and Fachrurazi (2022) dengan hasil yang beragam, namun penelitian tersebut tidak membahas ROE dan ukuran DPS. Berdasarkan temuan penelitian terdahulu yang menunjukkan hasil yang tidak konsisten dan terdapat perbedaan pembahasan dengan penelitian ini, sehingga posisi penelitian ini memiliki perbedaan dan kebaruan.…”
Section: Faktor-faktor Yang Mempengaruhi Pengungkapan Islamic Social ...unclassified
See 1 more Smart Citation